How to Subtract Algebraic Fractions (Mathematics Lesson)
Subtracting Algebraic Fractions
Imagine you wanted to subtract a⁄b and c⁄d.
How to Subtract Algebraic Fractions
To subtract algebraic fractions, use the rule:
A Real Example of How to Subtract Algebraic Fractions
An Example Question
Subtract the algebraic fractions below.
Compare the fractions you are subtracting with the rule shown above.
By comparing, we see that a = x, b = 2, c = y, d = 3.
Use the rule, with a = x, b = 2, c = y, d = 3:
Calculate the terms in the rule. Where we have written two numbers or letters in brackets together, multiply them together:
(x)(3) = x × 3 = 3x
(2)(y) = 2 × y = 2y
(2)(3) = 2 × 3 = 6
We have subtracted x⁄2 and y⁄3:
Another Real Example of How to Subtract Algebraic Fractions
The slider below shows a real example of how to subtract algebraic fractions.
Understanding The Rule
The letters written next to each other denotes that they are multiplying each other.
Make sure you can:
Why Does This Work?
When subtracting fractions (algebraic or not) all of the fractions must have a common denominator.
If initially the denominators are not the same...
...multiplying the denominators together will make a common denominator.
But having multiplied the denominator of each fraction, the numerator must be multiplied by the same value if we are not to change the fraction.
This gives us the rule for subtracting algebraic fractions: